2007
DOI: 10.1111/j.1365-2265.2007.02776.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating obestatin levels in normal subjects and in patients with impaired glucose regulation and type 2 diabetes mellitus

Abstract: Our results suggest that obestatin may play a role in appetite regulation in patients with IGR and T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
24
2
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 12 publications
9
24
2
5
Order By: Relevance
“…However, these findings were in agreement with a previous study (Qi et al 2007), which found that obestatin levels correlated inversely and significantly with BMI (P = 0.035), insulin (P = 0.003) and HOMA-IR (P = 0.031) values, and did not correlate significantly with age (P = 0.162) nor glucose (P = 0.162) in diabetic patients (but their patients were not obese) [20] A study by Ma et al 2014 found that plasma obestatin concentrations in diabetic patients were significantly lower than those in normal glucose tolerance subjects. This is consistent with our results, although, all their subjects were middle-aged (41-64 years) and old (65-76 years) and they were not obese, and they showed that plasma ghrelin was negatively associated with fasting glucose and Urine Albumin-to-Creatinine Ratio (UACR), so that the lower ghrelin levels might be a potential indicator for renal dysfunction in patients with T2D [21].…”
Section: Discussionsupporting
confidence: 65%
“…However, these findings were in agreement with a previous study (Qi et al 2007), which found that obestatin levels correlated inversely and significantly with BMI (P = 0.035), insulin (P = 0.003) and HOMA-IR (P = 0.031) values, and did not correlate significantly with age (P = 0.162) nor glucose (P = 0.162) in diabetic patients (but their patients were not obese) [20] A study by Ma et al 2014 found that plasma obestatin concentrations in diabetic patients were significantly lower than those in normal glucose tolerance subjects. This is consistent with our results, although, all their subjects were middle-aged (41-64 years) and old (65-76 years) and they were not obese, and they showed that plasma ghrelin was negatively associated with fasting glucose and Urine Albumin-to-Creatinine Ratio (UACR), so that the lower ghrelin levels might be a potential indicator for renal dysfunction in patients with T2D [21].…”
Section: Discussionsupporting
confidence: 65%
“…Using different prohormone convertases, Zhu et al were not able to observe the formation of obestatin from proghrelin [53]. In addition, plasma obestatin levels measured by radioimmunoassay (RIA) led to varying results which might indicate that the low specificity of these tests could be due to lacking standardization and imprecise values in previous studies [19,36].…”
Section: Discussionmentioning
confidence: 99%
“…It was originally suggested that obestatin binds to the orphan G protein-coupled receptor (GPR), named GPR39 (17). Increased obestatin, decreased ghrelin levels and a decreased ghrelin/obestatin ratio characterize obesity in women (18), and plasma obestatin levels are low in patients with type 2 diabetes mellitus and impaired glucose intolerance (19). Both obestatin and ghrelin levels are increased in anorexic subjects and decreased in human obesity, suggesting that obestatin is a nutritional marker reflecting body adiposity and insulin resistance.…”
Section: Various Formsmentioning
confidence: 99%